Patents of traditional medicine inventions and their relationship with traditional knowledge associated with genetic resources in Namibia: proposals for legal reform - Jacobs, Cislé Stella (Intellectual Property Research Unit, 2017)
The study recognises the significant biotechnical role of the pharmaceutical industry in developing and processing traditional medicine into safe and efficacious drugs and vaccines and how patent law assist this achieving this end. The study argues that patenting of traditional medicine inventions is possible without encroaching on the protection accorded to TK associated with GRs. It further argues that through the implementation of a disclosure requirement for all patent applications of inventions which are based on or derived from TK associated with GRs, misappropriation of TK and GRs can be prevented in Namibia. To this end, the study identifies key concepts and legal instruments both internationally and regionally i.e. the Convention on Biological Diversity, 1993, the TRIPS Agreement, 1994 and the Swakopmund Protocol on the Protection of Traditional Knowledge and Expressions of Folklore, 2010; which provides for TK, GRs and patent laws. The study further analysed how Namibia translated international obligations to its legal framework. A comparative analysis is produced between Namibia and South Africa to determine which system is most suitable for Namibia.